Evaluating Repeatability of RTK GPS/GLONASS Near/Under Forest Environment - Pirti, Atinc; Gumus, Kutalmis; Erkaya, Halil; Hosbas, Ramazan Gursel (CROATION FORESTS, 2010)
Until the mid-1990s, post-processing was the only method available to determine survey-grade positions using GPS A new method was then introduced called Real-Tune Kinematic (RTK) Real Time Kinematic surveying is an advanced form of relative GPS carrier phase surveying in which the base station transmits its raw measurement data to rovers, which then compute a vector baseline from the base station to the rover. RTK GPS shows a really efficient and fast improvement within today's technological developments The most important reason for using it is that this technique enables obtaining coordinates instantaneously and in the centimeter level accuracy. This technique is widely used in construction and survey applications because of its above mentioned properties. The aim of this paper is to evaluate the repeatability of RTK measurement accuracy under different satellite configurations near/in forest and unobstructed environments. Testing was performed by using GPS+GLONASS receivers under these conditions, i.e. tall trees forest and unobstructed areas The obtained results of RTK testing were compared with results of total station surveying as a further quality check Nevertheless, it appears that RTK measurements under forest environment with 1 cm accuracy cannot be guaranteed on all occasions, since difficult situations may lead to greater errors These results indicate that integrating RTK GPS/GLONASS system with total station is favored for surveying under forest environment
Keywords: RTK GPS/GLONASS; Forest Environment; Total Station; Accuracy; Forestry